2019
DOI: 10.1155/2019/7090767
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in Unexplained Recurrent Spontaneous Abortions and Their Diagnostic Potential

Abstract: Unexplained recurrent spontaneous abortion (URSA) is defined as the loss of two or more consecutive pregnancies before the 20th week of gestation with normal findings on routine screening tests. Our understanding of the cellular and molecular pathogenesis of URSA is still far from complete. Noncoding RNAs (ncRNAs) play a pivotal role in transcription and expression. The functions of ncRNAs may also improve understanding of URSA pathogenesis. Because of their stability in the circulatory system and at the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Various therapeutic strategies such as immunologic intervention with allogenic lymphocyte [ 9 ] and immunoglobulin [ 10 ], anticoagulant therapy using aspirin [ 11 ] or low-molecular weight heparin [ 12 ], hormonal supplementation with progesterone or dydrogesterone [ 13 ], and microelements supplementation, such as vitamin E, vitamin D [ 14 ], and folic acid [ 15 ], have been used to improve pregnancy outcomes among these women, but no effective treatment has been identified. To date, there is no widely accepted therapeutic approaches for URSA [ 16 ], bringing seriously physical and mental impacts to both the affected female population and their families [ 17 19 ]. Therefore, it is essential to investigate effective treatments to reduce pregnancy losses and maintain successful pregnancy preservation in patients with URSA.…”
Section: Introductionmentioning
confidence: 99%
“…Various therapeutic strategies such as immunologic intervention with allogenic lymphocyte [ 9 ] and immunoglobulin [ 10 ], anticoagulant therapy using aspirin [ 11 ] or low-molecular weight heparin [ 12 ], hormonal supplementation with progesterone or dydrogesterone [ 13 ], and microelements supplementation, such as vitamin E, vitamin D [ 14 ], and folic acid [ 15 ], have been used to improve pregnancy outcomes among these women, but no effective treatment has been identified. To date, there is no widely accepted therapeutic approaches for URSA [ 16 ], bringing seriously physical and mental impacts to both the affected female population and their families [ 17 19 ]. Therefore, it is essential to investigate effective treatments to reduce pregnancy losses and maintain successful pregnancy preservation in patients with URSA.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al exhibited higher expression of HOTAIR in RSA patients compared with healthy controls 63 . Interestingly, it is reported that HOTAIR can be suppressed in RSA 64 . This might affect trophoblast invasion and alter the expression pattern of MMP9 , 24,65 a gene that is upregulated in RSA patients 66 .…”
Section: Discussionmentioning
confidence: 99%
“… 39 It is well accepted that gene expression is altered in trophoblast cells of women with URSA. 40 , 41 However, to date, the circRNAs and their related ceRNA networks in URSA are largely unknown. In this study, we demonstrate a global circRNA-miRNA-mRNA network for the first time, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%